Delayed Diagnosis and Evolving Trends in Gastric Cancer During and After COVID-19: A Comparative Study of Staging, Helicobacter pylori Infection and Bleeding Risk in Western Romania - Patricia Serena; Bogdan Miutescu; Eyad Gadour; Calin Burciu; Ruxandra Mare; Renata Bende; Edward Seclăman; Giovanni Aragona; Luca Serena; Roxana Sirli (Diagnostics)
Background and Objectives: Gastric cancer (GC) remains a leading cause of cancer mortality worldwide, and the COVID-19 pandemic posed new barriers in diagnosis and management. This study aimed to assess whether pandemic-related healthcare disruptions resulted in more advanced GC stages at presentation. We additionally examined the role of Helicobacter pylori (H. pylori) across non-cardia GC (NCGC) versus cardia GC (CGC) and evaluated the risk factors of upper gastrointestinal (GI) bleeding. Methods: A retrospective cohort of 121 adult patients with GC was enrolled from a tertiary Gastroenterology Unit in Western Romania, spanning pre-pandemic (March 2018–February 2020), pandemic (March 2020–February 2022), and post-pandemic (March 2022–February 2024) periods. Demographic profiles, TNM staging, histopathology, H. pylori status, and clinical outcomes—including GI bleeding—were extracted from medical records. Results: An increase in advanced GC (Stage III–IVB) was noted in the post-pandemic period (69.4% vs. 53.3% pre-pandemic; p = 0.021). H. pylori positivity remained higher in NCGC (70.6%) compared to CGC (44.6%; overall p = 0.041); however, CGC cases showed a rise in H. pylori prevalence post-pandemic (36.4% to 55.6%). One-year mortality was driven by an advanced stage (hazard ratio [HR] = 2.74, p = 0.002), diagnosis during the COVID-19 pandemic (HR = 1.66, p = 0.010), and age ≥70 years (HR = 1.88, p = 0.043). Conclusions: Our findings demonstrate that delayed diagnostic endoscopy correlated with a higher proportion of advanced GC in the post-pandemic phase. H. pylori was strongly linked to NCGC, though CGC showed an increasing trend in H. pylori prevalence. Patients on antithrombotic agents faced increased GI bleeding risks.